2021
DOI: 10.1021/acsaem.1c01975
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Effect in BODIPY-(Zn)Porphyrin Entities Promotes H2 Evolution in Dye-Sensitized Photocatalytic Systems

Abstract: In this study, we report the utilization of BODIPY-(Zn)­Porphyrin hybrids in photocatalytic H2 production from water. These entities were applied as photosensitizers upon their chemisorption onto the surface of platinum-doped titanium dioxide nanoparticles (Pt-TiO2), which acted as photocatalysts. To evaluate the impact of the different connectivity between the chromophores in photocatalytic in H2 evolution, we employed two diverse BODIPY-(Zn)­Porphyrin entities, in which the BODIPY moiety is either covalently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…37) and their application in photocatalytic H 2 production from water utilizing platinum-doped titanium dioxide nanoparticles (PtTiO 2 ). 167 More specifically the hybrid photosensitizers were employed in a dye-sensitized photocatalytic system (DSP) after their chemisorption onto the surface of the PtTiO 2 . The authors showed that the covalent attachment of the BDP moiety (BDP-Por) illustrated greater efficiency (17 500 TONs) compared to the axial coordination (BDP(Im)-Por, 13 700 TONs) while the triad system BDP-Por-BDP(Im) overwhelmed the other hybrids in terms of activity (18 600 TONs).…”
Section: Review Articlementioning
confidence: 99%
“…37) and their application in photocatalytic H 2 production from water utilizing platinum-doped titanium dioxide nanoparticles (PtTiO 2 ). 167 More specifically the hybrid photosensitizers were employed in a dye-sensitized photocatalytic system (DSP) after their chemisorption onto the surface of the PtTiO 2 . The authors showed that the covalent attachment of the BDP moiety (BDP-Por) illustrated greater efficiency (17 500 TONs) compared to the axial coordination (BDP(Im)-Por, 13 700 TONs) while the triad system BDP-Por-BDP(Im) overwhelmed the other hybrids in terms of activity (18 600 TONs).…”
Section: Review Articlementioning
confidence: 99%
“…The development of robust photocatalysts for efficient harvesting of broadband solar radiation, particularly near-infrared wavelengths, is essential for the solar-to-fuel technology. Most commonly used semiconductor-based photocatalysts operate in the UV and visible wavelengths. two-dimensional (2D)-nanomaterial-based photocatalysts enhance the charge transfer kinetics and surface activity due to high surface-to-volume ratios, and the light harvesting can be extended; however, it requires a complex preparation process. Organic molecules provide the wavelength flexibility, but they also suffer from acute photobleaching. , Plasmonic nanoparticles have recently emerged as potential photocatalysts for visible as well as near-infrared (NIR) wavelengths due to their tunable plasmon resonance wavelengths across the visible and NIR spectral range. The surface plasmon resonance (SPR) of a plasmonic nanostructure is sensitive toward its size, shape, and the surrounding dielectric environment. , The SPR band of isotropic nanostructures such as gold nanospheres (AuNSs) can be tuned in the range of 500–580 nm, while that of anisotropic nanostructures such as nanorods and nanoprisms is tunable over the entire visible–NIR wavelength ranges, providing an opportunity to harvest photons from the entire visible–NIR region. ,, The photoexcitation of the surface plasmons creates energetic charge carriers, commonly known as hot carriers. These charge carriers can initiate and enhance a chemical reaction on the surface of these nanoparticles. However, the incident photon-to-chemical conversio...…”
Section: Introductionmentioning
confidence: 99%
“…The binary system composed of different chromophores undergoing the energy transfer process can be used for light harvesting and has important applications in the field of photocatalysis. For example, Coutsolelos and co‐workers [ 233 ] developed a highly efficient dye‐sensitized photocatalytic systems based on a noble metal free PS BODIPY–(Zn)porphyrin hybrids (Figure 7f). The BODIPY–(Zn)porphyrin entities, which were chemically adsorbed on platinum‐doped‐titanium dioxide NPs, were used as the PSs for hydrogen precipitation.…”
Section: Assembly Models Of Bodipymentioning
confidence: 99%
“…f) BODIPY-(Zn)porphyrin hybrids as PSs in photocatalytic H 2 production from water (BDP: covalently attached BODIPY, BDP(Im): axially coordinated BODIPY, Por: (Zn)porphyrin). Reproduced with permission [233]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%